MEASUREMENT OF SOIL-WATER CHARACTERISTIC CURVE (SWCC) BEYOND RESIDUAL SUCTION FOR SHALE IN CISOMANG AND DEVELOPMENT OF REGRESSION METHOD FOR SOIL-WATER CHARACTERISTIC CURVE (SWCC) EQUATION OF FREDLUND AND XING (1994) - Anisa Fanani, Maudy
The development of geotechnical engineering finds that not all soil conditions can be quantified by saturated soil mechanics or classical soil mechanics. One method to quantify unsaturated soil mechanics problems is soil-water characteristic curve (SWCC). The commonly used method for measuring SWCC is the filter paper method. Measurement with filter paper method is carried out by arranging soil samples with filter paper and allowing them to quilibrate for a certain period of time. Calibration is done with the Leong calibration curve based on the measurement of water content on the filter paper to measure the value of matric suction. The values of water content at equilibrium conditions and the corresponding matric suction values are then combined to form the soil-water characteristic curve. In this study, the wetting and drying soil-water characteristic curves were measured for clay shale soil in the residual matric suction range with a water content of 1-3%. Verification and comparison of laboratory test results were conducted using a numerical method with SEEP/W and FORTRAN program to determine the best-fit curve. The determination of the best-fit curve was based on the Fredlund and Xing SWCC equation (1994), and the numerical calculations were performed using a bruteforce method to find the best-fit parameters that produced the smallest sum-square error. This research investigates the mathematical behavior of the Fredlund and Xing SWCC equation to develop a simpler calculation method. The laboratory testing results yielded an equilibrium time of 21 days for wetting at a water content of 1% and 20 days at a water content of 3%. The SEEP/W modeling resulted in an equilibrium time of 20 days for wetting at a water content of 1% and 18 days for wetting at a water content of 3%. The drying measurement at a water content of 2% obtained from laboratory testing was 7-21 days. However, the investigation of the mathematical behavior of the Fredlund and Xing SWCC equation (1994) could not be approached using the steepest descent method, requiring further research with a different approach.